Treatment of infectious process injury by erisipela: Experience report - Meneses, Arthur Bento de; Rodrigues, Cinthia Sonaly Santos; Sousa, Marina Sandrelle Correia de; Castilho, João Cezar; Oliveira, Pedro Gonçalves de (Revista Feridas, 2019)
Erysipelas is an infectious process commonly caused by bacteria from Streptococcus family. Treatment is instituted by using specific antibiotics and special dressings applied on affected areas. Comorbidities such as hypertension and diabetes mellitus can impair the healing process. The aim of this study was to report the experience of treating a patient with ulcers resulting from an erysipelas infectious process. This is an exploratory descriptive, case report, of a patient assisted by a wound care specialized clinic located in the city of Campina Grande - PB. A 36-year-old female patient with hypertension and non-insulin-dependent diabetes mellitus. On physical examination, she was oriented, hydrated, sedentary, with preserved motor force and reporting exacerbated pain. She presented superficial and infected lesions due to erysipelas, located in the left lower limb and evidences of diffuse hyperemia, presence of blisters and necrosis points. As initial conduct, antibiogram culture of the material removed from the lesions was requested. The dressing was performed by aseptic technique and cleaning with deionized water and antiseptic biguanide polyhexamethylene (PHMB) based soap. To the dressing were added pads soaked in potassium permanganate solution and placed on the lesions for 24 hours. Subsequently, a protocol was initiated using 0.2% hyaluronic acid cream to stimulate skin regeneration and favor angiogenesis, betamethasone dipropionate ointment to relieve pruritus and other symptoms associated with the infectious process, and potassium permanganate solution, aiming at the destruction of the bacterial wall, associated with the use of sterile PHMB-impregnated cotton gauze, both allied to the use of systemic antibiotic therapy. The treatment lasted 35 days, with 9 applications. After this period, the wound was considered healed, with no diffuse hyperemia, blisters, edema or darkened regions of the skin, and complete remission of the infectious process. It was possible to observe the effectiveness of the treatment performed, taking into consideration factors such as the established conduct plan, the products used, the multiprofessional perspective and the good patient compliance.